A case of acute mercury vapour poisoning. Issue 596 (June 1975) - Eastmond, C. J.; Holt, S.
Abstract : A case is reported of a research chemist who was briefly exposed to a high concentration of mercury vapour and who developed symptoms of systemic poisoning, but who had a normal urinary excretion of mercury. This latter is not considered to refute the diagnosis. The literature is briefly reviewed.